Method for applying laser annealing technology to edge passivation of half cell

The AlOx film deposited by ALD is annealed through laser annealing technology, which solves the problems of long process time and high energy consumption in the prior art, and achieves efficient battery edge passivation, and obtains high-quality AlOx films and better performance.

CN119653904APending Publication Date: 2025-03-18JIETAI NEW ENERGY TECHNOLOGY (SUZHOU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411765108.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When the prior art passivates the edge of half a battery, the process time is long and the energy consumption is high, resulting in stress generated during the high-temperature annealing process, making it difficult to form a dense film, and lattice mismatch and defects occur.

Method used

The AlOx film deposited by ALD deposition method is annealed by laser annealing technology, and a temperature step is formed through pulsed laser and atomized cooling, local heating and rapid cooling of the battery surface to improve the crystal structure and performance.

Benefits of technology

It realizes improving the battery edge passivation performance in a short time, reducing the pFF loss of half a battery, and reducing process time and energy consumption, and obtaining a high-quality AlOx film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653904A_ABST
    Figure CN119653904A_ABST
Patent Text Reader

Abstract

The invention relates to a method for applying a laser annealing technology to edge passivation of a half-piece battery, which is applied to the technical field of battery passivation and comprises the following steps of: forming end slots at two ends of a battery parting line by using pulse laser, and cutting the slotted battery by using a temperature step of laser heating and atomization cooling to obtain the half-piece battery; stacking and pressing the dried half cells, placing the half cells into a coating material box, and carrying out AlOx film layer deposition on the cutting surfaces of the half cells by using an ALD deposition method; and carrying out laser annealing treatment along the cutting surface of the half-piece cell, which is subjected to AlOx film layer deposition, by using a laser beam to finish edge passivation. The method has the advantages that the passivation performance can be improved, the process time is shortened, the energy consumption is reduced, and the edge of the battery is passivated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery passivation, and in particular to a method for applying laser annealing technology to edge passivation of a half-cell battery. Background Art

[0002] With the popularization of cell slicing, shingling, and cell joining and splicing technologies, the use of lasers to cut whole cells has gradually become the mainstream trend in the industry. For half-cells, laser cutting will cause serious laser damage and interface defects, thus forming effective carrier recombination centers, causing edge recombination losses, and thus leading to efficiency losses of crystalline silicon solar cells.

[0003] To solve this problem, the existing technology usually uses a thermal atomic layer deposition method (ALD) to deposit an AlOx film on the cut surface to reduce edge carrier recombination and improve the edge passivation performance of the cut battery. However, the AlOx film deposited by ALD usually requires a long period of high-temperature annealing to obtain a high-quality film. However, long-term high-temperature annealing will increase the process time and bring a lot of energy consumption. On the other hand, the stress generated between AlOx and the silicon wafer substrate at the edge of the slice during the long high-temperature annealing process will make it difficult to form a dense AlOx film, and the AlOx lattice will be mismatched and defects will be generated. There is an urgent need for a battery edge passivation technology that can improve the passivation performance while reducing the process time and energy consumption. Summary of the invention

[0004] In order to improve the passivation performance while reducing the process time and energy consumption to passivate the edge of the battery, the present application provides a method for applying laser annealing technology to the edge passivation of a half-cell battery.

[0005] In a first aspect, the present application provides a method for applying laser annealing technology to edge passivation of a half-cell battery, using the following technical solution:

[0006] A method for applying laser annealing technology to edge passivation of a half-cell battery, comprising:

[0007] Use pulsed laser to make grooves at both ends of the battery dividing line, and use the temperature gradient of laser heating and atomization cooling to cut the grooved battery to obtain half-cell batteries;

[0008] The dried half-cell batteries are stacked and pressed into a coating material box, and AlOx film is deposited on the cut surface of the half-cell batteries using the ALD deposition method;

[0009] The cut surface where the AlOx film is deposited is laser annealed along the half-cell using a laser beam to complete edge passivation.

[0010] Optionally, a continuous laser with a power of 50w infrared pulse + 300w infrared continuous power is used to reserve 30% of the power, and the battery is heated to 180-300°C for 0.7 seconds and then atomized and cooled to form a temperature ladder.

[0011] Optionally, the ALD deposition method uses N2 as the isolation gas and adopts trimethylaluminum and water to react to deposit an AlOx film on the cut surface of the half-cell.

[0012] Optionally, the deposition temperature of the AlOx film layer is 220° C., with a fluctuation range of ±10° C.

[0013] Optionally, the laser beam adopts an excimer laser, and the shape of the laser beam is a rectangle of 380um×150um.

[0014] Optionally, the pulse width of the laser is 20ns, the average number of pulses per point is 8, the energy density is 1-3J / cm2, and the scanning speed is 5mm / s.

[0015] Optionally, a corrosive solution is used to etch the cut edge of the half-cell battery to cut off the laser damaged portion of the half-cell battery.

[0016] Optionally, the corrosion solution does not exceed the position of the first secondary grid line at the cut edge of the half-cell.

[0017] Optionally, the cut edges of the half-cell after etching are cleaned with pure water, and the cleaned cut edges are dried.

[0018] Optionally, the laser annealed half-cell batteries are tested and sorted, and packaged according to the test and sorting results.

[0019] In summary, the present application includes at least one of the following beneficial technical effects:

[0020] Laser annealing technology and ALD deposition method are used to anneal the AlOx film layer deposited on the cut surface of the half-cell battery. The energy of the laser beam is converted into thermal energy through light-matter interaction, locally heating the battery surface, causing the local temperature of the battery surface to rise. Subsequently, the temperature of the battery surface will quickly rise to the high-temperature area, and then quickly cool down under the action of atomization, thereby changing the crystal structure and performance of the battery, so that high-quality AlOx film can be obtained, the passivation performance can be improved, and the pFF loss of the half-cell battery can be reduced. In addition, the overall execution is fast and simple, which can reduce the process time and save energy consumption, so that the battery edge can be passivated while improving the passivation performance and reducing the process time and energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1It is a schematic diagram of the structure of laser annealing in an embodiment of the present application.

[0022] Figure 2 It is a structural schematic diagram of the embodiment of the present application reflecting the SEM test laser annealing effect.

[0023] Figure 3 It is a structural schematic diagram of an embodiment of the present application that reflects the effect of ordinary annealing tested by SEM. DETAILED DESCRIPTION

[0024] The following is combined with Figure 1-3 This application is described in further detail.

[0025] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0027] In addition, the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article, unless otherwise specified, generally means that the associated objects before and after are in an "or" relationship.

[0028] The present application provides a method for applying laser annealing technology to edge passivation of a half-cell battery, comprising:

[0029] S1: Use pulsed laser to open grooves at both ends of the battery dividing line, and use the temperature gradient of laser heating and atomization cooling to cut the grooved battery to obtain half-cell batteries;

[0030] S2: stack the dried half-cell batteries and press them into a coating material box, and deposit an AlOx film on the cut surface of the half-cell batteries using an ALD deposition method;

[0031] S3: Use a laser beam to perform laser annealing along the cut surface of the half-cell where the AlOx film is deposited to complete edge passivation.

[0032] In this embodiment, the battery that uses pulse laser to open end grooves is a whole piece of finished crystalline battery cell. The whole piece of initial battery cell is cut by pulse laser at both ends of the battery dividing line to cut open end grooves. The battery is heated along the two open end grooves, and after the heating time is over, atomization cooling is added to form a temperature step, so that the battery breaks, thereby completing the cutting to obtain a half-cell battery.

[0033] In this embodiment, step S1 can use any pulse laser to open the groove and laser deheat. Optionally, a continuous laser with a power reserve of 30% and a parameter of 50w infrared pulse + 300w infrared continuous is used to heat the battery for 0.7 seconds and then perform atomization cooling to form a temperature ladder, wherein the temperature of the heated battery is 180-300°C. Optionally, the temperature of the heated battery can be 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 236°C, 237°C, 238°C, 239°C, 240°C, 241°C, 242°C, 243°C, 244°C, 245°C, 246°C, 247°C, 248°C, 249°C, 250°C, 251°C, 252°C, 253°C, 254°C, 256°C, 257°C, 258°C, 259°C, 260°C, 261°C, 262°C, 263°C, 264°C, 265°C, 266°C, 267°C, 268°C, 269°C, 270°C, 271°C, 272°C, 273°C, 274°C, 275°C, 276°C, 277°C, 278°C, 279°C, 280°C, 281°C, 28 20℃, 225℃, 230℃, 235℃, 240℃, 245℃, 250℃, 255℃, 260℃, 265℃, 270℃, 275℃, 280℃, 285℃, 290℃, 295℃, 300℃ or any value in between, high-energy laser irradiation of the battery causes partial melting and vaporization of the battery, and after increasing water atomization, that is, increasing atomization cooling, the temperature of the battery can be instantly reduced, resulting in a temperature step, that is, a temperature difference, and the stress generated by the temperature difference is used to split the battery.

[0034] In this embodiment, step S2 can compress the stack and place it in a coated metal box to use the ALD deposition method to deposit an AlOx film. Optionally, the coated metal box can be an aluminum box. In step S2, the AlOx film is deposited by the ALD deposition method using N2 as an isolation gas, and the AlOx film is deposited on the cut surface of the half-cell battery by reacting trimethylaluminum with water, wherein the reaction of trimethylaluminum with water can be replaced by other reactions with the same effect. Optionally, similar hydroxides and hydrocarbon products can be used for reaction, such as using dimethylaluminum to react with water, ethylaluminum to react with water, etc.

[0035] In this embodiment, the deposition temperature of the AlOx film layer is 220°C, with a fluctuation range of ±10°C. The deposition temperature of the AlOx film layer can be 210°C, 215°C, 220°C, 225°C, 230°C or any value therebetween.

[0036] In this embodiment, in step S3, a laser beam generated by any laser can be used to perform laser annealing along the cut surface of the half-cell battery for AlOx film deposition. Optionally, the laser can be an excimer laser. In step S3, when the laser beam performs laser annealing along the cut surface of the half-cell battery for AlOx film deposition, the laser beam needs to cover the cut surface. The laser beam can be in any shape, such as Figure 1 As shown, the laser beam adopts a rectangular beam, and optionally, the laser beam shape is a rectangle of 380um×150um. The pulse width of the laser is 20ns, the average number of pulses per point is 8, the energy density is 1-3J / cm2, and the scanning speed is 5mm / s.

[0037] In this embodiment, during the laser annealing process, a local temperature gradient is generated on the surface of the AlOx film, and large particles absorb more energy than small particles and have a higher temperature, which can induce the selective growth of large particles. However, in traditional high-temperature annealing, heat is transferred from the substrate at the bottom of the material box to the AlOx film at the top, and the heat can be uniformly absorbed by the AlOx film, resulting in smaller particles and higher density during the annealing process. Therefore, the laser annealing method can produce larger grains than traditional high-temperature annealing, and the surface quality of the AlOx film is better and the surface is uniform.

[0038] In this embodiment, between step S1 and step S2, a corrosive solution can also be used to etch the cut edge of the half-cell battery to cut off the laser damaged portion of the half-cell battery, wherein the corrosive solution is an alkaline solution, and the optional corrosive alkaline solution can be sodium hydroxide, potassium hydroxide, barium hydroxide, ammonium hydroxide, calcium hydroxide, lithium hydroxide, rubidium hydroxide, cesium hydroxide or other alkaline solutions.

[0039] In this embodiment, the corrosion solution does not exceed the position of the first secondary grid line at the cut edge of the half-cell. Since the corrosion solution is an alkaline solution, exceeding the position of the first grid line will corrode the silver paste in the battery, bringing negative effects.

[0040] In this embodiment, pure water is used to clean the cut edge of the half-cell after etching, and the cleaned cut edge is dried. The drying is to dry the water on the cut edge of the half-cell. The temperature is about 160°C. The drying temperature can be adjusted according to the on-site process conditions. The specific adjustment method is to adjust dynamically according to the on-site process at any time.

[0041] In this embodiment, the laser annealed half-cells are tested and sorted, and then packaged according to the test and sorting results.

[0042] Example 1

[0043] S1: Use pulse laser to open grooves at both ends of the battery dividing line, using parameters of 50w, infrared pulse + 300w infrared continuous, 30% laser power reserved, lasting for 0.7 seconds, heating the battery to 300℃ and atomizing cooling temperature step to cut the grooved battery to obtain half-cell batteries;

[0044] S2: stack and press the dried half-cell batteries into a rate box, and deposit an AlOx film on the cut surface of the half-cell batteries at 220°C using an ALD deposition method;

[0045] S3: Use an excimer laser with a pulse width of 20ns, an average number of pulses per point of 8, an energy density of 1-3J / cm2, a scanning speed of 5mm / s, and a rectangular laser beam with a shape of 380um×150um to perform laser annealing along the cut surface of the half-cell where the AlOx film is deposited to complete edge passivation.

[0046] Example 2

[0047] S1: Use pulse laser to open grooves at both ends of the battery dividing line, using parameters of 50w, infrared pulse + 300w infrared continuous, 30% laser power reserved, lasting for 0.7 seconds, heating the battery to 200℃ and atomizing cooling temperature step to cut the grooved battery to obtain half-cell batteries;

[0048] S2: stack and press the dried half-cell batteries into a rate box, and deposit an AlOx film on the cut surface of the half-cell batteries at 220°C using an ALD deposition method;

[0049] S3: Use an excimer laser with a pulse width of 20ns, an average number of pulses per point of 8, an energy density of 1-3J / cm2, a scanning speed of 5mm / s, and a rectangular laser beam with a shape of 380um×150um to perform laser annealing along the cut surface of the half-cell where the AlOx film is deposited to complete edge passivation.

[0050] Example 3

[0051] S1: Use pulse laser to open grooves at both ends of the battery dividing line, using parameters of 50w, infrared pulse + 300w infrared continuous, 30% laser power reserved, lasting for 0.7 seconds, heating the battery to 300℃ and atomizing cooling temperature step to cut the grooved battery to obtain half-cell batteries;

[0052] S2: stack and press the dried half-cell batteries into a rate box, and deposit an AlOx film on the cut surface of the half-cell batteries at 210°C using an ALD deposition method;

[0053] S3: Use an excimer laser with a pulse width of 20ns, an average number of pulses per point of 8, an energy density of 1-3J / cm2, a scanning speed of 5mm / s, and a rectangular laser beam with a shape of 380um×150um to perform laser annealing along the cut surface of the half-cell where the AlOx film is deposited to complete edge passivation.

[0054] Example 4

[0055] S1: Use pulse laser to open grooves at both ends of the battery dividing line, using parameters of 50w, infrared pulse + 300w infrared continuous, 30% laser power reserved, lasting for 0.7 seconds, heating the battery to 300℃ and atomizing cooling temperature step to cut the grooved battery to obtain half-cell batteries;

[0056] S2: stack and press the dried half-cell batteries into a rate box, and deposit an AlOx film on the cut surface of the half-cell batteries at 220°C using an ALD deposition method;

[0057] S3: Use an excimer laser with a pulse width of 20ns, an average number of pulses per point of 8, an energy density of 1-3J / cm2, a scanning speed of 5mm / s, and a rectangular laser beam with a shape of 400um×150um to perform laser annealing along the cut surface of the half-cell where the AlOx film is deposited to complete edge passivation.

[0058] Example 5

[0059] S1: Use pulse laser to open grooves at both ends of the battery dividing line, using parameters of 50w, infrared pulse + 300w infrared continuous, 30% laser power reserved, lasting for 0.7 seconds, heating the battery to 300℃ and atomizing cooling temperature step to cut the grooved battery to obtain half-cell batteries;

[0060] S2: etching the cut edge of the half-cell battery with a corrosive solution, cutting off the laser damaged portion of the half-cell battery, cleaning the cut edge of the half-cell battery after etching with pure water, and drying the cleaned cut edge;

[0061] S3: stack and press the dried half-cell batteries into a rate box, and deposit an AlOx film on the cut surface of the half-cell batteries at 220°C using an ALD deposition method;

[0062] S4: Use an excimer laser with a pulse width of 20ns, an average number of pulses per point of 8, an energy density of 1-3J / cm2, a scanning speed of 5mm / s, and a rectangular laser beam with a shape of 380um×150um to perform laser annealing along the cut surface of the half-cell where the AlOx film is deposited to complete edge passivation.

[0063] Comparative Example 1

[0064] S1: Use pulse laser to open grooves at both ends of the battery dividing line, using parameters of 50w, infrared pulse + 300w infrared continuous, 30% laser power reserved, lasting for 0.7 seconds, heating the battery to 300℃ and atomizing cooling temperature step to cut the grooved battery to obtain half-cell batteries;

[0065] Comparative Example 2

[0066] S1: Use pulse laser to open grooves at both ends of the battery dividing line, using parameters of 50w, infrared pulse + 300w infrared continuous, 30% laser power reserved, lasting for 0.7 seconds, heating the battery to 300℃ and atomizing cooling temperature step to cut the grooved battery to obtain half-cell batteries;

[0067] S2: stack and press the dried half-cell batteries into a rate box, and deposit an AlOx film on the cut surface of the half-cell batteries at 220°C using an ALD deposition method;

[0068] S3: Use traditional high temperature laser annealing to treat the cut surface of the half-cell where the AlOx film is deposited to complete edge passivation.

[0069] Performance Testing

[0070] Reference Figure 2 and Figure 3 , Table 1 and Table 2, Table 1 is the SunsVoc test results, Table 2 is the group power test results.

[0071] Table 1

[0072]

[0073] Table 2

[0074] Sample Voc Isc Vpm Ipm Rs R Pmax FF Comparison 1 53.18 13.750 45.44 13.105 0.33 776.68 595.54 81.44% Comparison 2 53.24 13.773 45.41 13.200 0.34 580.98 599.41 81.74% Example 1 53.25 13.772 45.63 13.172 0.33 688.96 601.06 81.97% Example 2 53.25 13.772 45.63 13.172 0.33 688.96 601.06 81.97% Example 3 53.24 13.773 45.41 13.200 0.34 580.98 599.41 81.74% Example 4 53.29 13.782 45.99 13.098 0.34 565.12 602.36 82.02% Example 5 53.33 13.778 45.60 13.219 0.33 549.29 602.77 82.03%

[0075] Among them, comparison 1 is a half-cell battery without AlOx edge passivation after dicing; comparison 2 is a half-cell battery with AlOx annealed by traditional high-temperature annealing; the experiment is a half-cell battery with AlOx annealed by laser annealing.

[0076] pass Figure 1 , Figure 2 , Figure 3As can be seen from Table 1 and Table 2, by using a pulse laser to open grooves at both ends of the battery dividing line, the parameters are 50w, infrared pulse + 300w infrared continuous, 30% laser power is reserved, and it lasts for 0.7 seconds. The battery is heated to 300℃ and the temperature step of atomization cooling is used to cut the grooved battery to obtain a half-cell battery; the dried half-cell batteries are stacked and pressed into a rate material box, and the AlOx film is deposited on the cut surface of the half-cell battery at 220℃ by the ALD deposition method; a pulse width of 20ns, an average number of pulses per point of 8, an energy density of 1-3J / cm2, a scanning speed of 5mm / s, and a rectangular laser beam with a shape of 380um×150um are used to perform laser annealing along the cut surface of the half-cell battery where the AlOx film is deposited. After the edge passivation treatment, the AlOx film of the half-cell battery has higher quality and better performance.

[0077] By using laser annealing technology to anneal the AlOx film layer deposited on the cut surface by the ALD deposition method, high-quality AlOx film can be obtained, the passivation performance can be improved, and the pFF loss of the half-cell battery can be reduced. In addition, compared with the traditional annealing process, the process time can be reduced and energy consumption can be saved.

[0078] The terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not expressly listed, or also includes elements inherent to such process, method, article, or apparatus.

[0079] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of application involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the aforementioned application concept. For example, the above features are replaced with (but not limited to) technical features with similar functions applied in the present application.

Claims

1. A method for applying laser annealing technology to edge passivation of a half-cell battery, characterized in that: include: Use pulsed laser to make grooves at both ends of the battery dividing line, and use the temperature gradient of laser heating and atomization cooling to cut the grooved battery to obtain half-cell batteries; The dried half-cell batteries are stacked and pressed into a coating material box, and AlOx film is deposited on the cut surface of the half-cell batteries using the ALD deposition method; The cut surface where the AlOx film is deposited is laser annealed along the half-cell using a laser beam to complete edge passivation.

2. The method according to claim 1, characterized in that The parameters are 50w infrared pulse + 300w infrared continuous power with 30% of continuous laser reserved, which lasts for 0.7 seconds to heat the battery to 180-300℃ and then perform atomization cooling to form a temperature ladder.

3. The method according to claim 1, characterized in that The ALD deposition method uses N2 as an isolation gas and uses trimethylaluminum and water to react to deposit an AlOx film on the cut surface of a half-cell.

4. The method according to claim 1, characterized in that: The deposition temperature of the AlOx film layer is 220°C, with a fluctuation range of ±10°C.

5. The method according to claim 1, characterized in that: The laser beam adopts an excimer laser, and the shape of the laser beam is a rectangle of 380um×150um.

6. The method according to claim 5, characterized in that The pulse width of the laser is 20ns, the average number of pulses per point is 8, the energy density is 1-3J / cm2, and the scanning speed is 5mm / s.

7. The method according to claim 1, characterized in that The cut edge of the half-cell battery is etched with a corrosive solution to cut off the laser damaged portion of the half-cell battery.

8. The method according to claim 7, characterized in that The etching solution does not exceed the position of the first secondary grid line at the cut edge of the half-cell.

9. The method according to claim 7, characterized in that: The etched cut edges of the half-cell are cleaned with pure water, and the cleaned cut edges are dried.

10. The method according to claim 1, characterized in that The laser annealed half-cell batteries are tested and sorted, and packaged according to the test and sorting results.

Citation Information

Cited By

  • Method for improving and processing Topcon battery low-efficiency piece and battery assembly of Topcon battery low-efficiency piece

    CN120500137A